The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1111/1462-2920.14024
|View full text |Cite
|
Sign up to set email alerts
|

Tales from the tomb: the microbial ecology of exposed rock surfaces

Abstract: Although a broad diversity of eukaryotic and bacterial taxa reside on rock surfaces where they can influence the weathering of rocks and minerals, these communities and their contributions to mineral weathering remain poorly resolved. To build a more comprehensive understanding of the diversity, ecology and potential functional attributes of microbial communities living on rock, we sampled 149 tombstones across three continents and analysed their bacterial and eukaryotic communities via marker gene and shotgun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 75 publications
(110 reference statements)
2
37
1
Order By: Relevance
“…Similarly, the observed dominance of Gemmatimonadetes in the edaphic niche, supported by previous findings by Niederberger et al (2008) and Babalola et al (2009), may be linked to their important role in soil biogeochemical processes through phosphorous metabolism (Zhang et al, 2003), hence assisting early ecosystem development in this deglaciated area (Knelman et al, 2014), as confirmed by the observed increases in soil phosphate availability with time. In contrast, the phylum Deinococcus-Thermus and the Sphingomonadales (Alphaproteobacteria) were significantly more abundant on rocks, where they may benefit from using sugar alcohols and organic acids released by lichenized fungi, molds and algae (Siebert and Hirsch, 1988;Brewer and Fierer, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the observed dominance of Gemmatimonadetes in the edaphic niche, supported by previous findings by Niederberger et al (2008) and Babalola et al (2009), may be linked to their important role in soil biogeochemical processes through phosphorous metabolism (Zhang et al, 2003), hence assisting early ecosystem development in this deglaciated area (Knelman et al, 2014), as confirmed by the observed increases in soil phosphate availability with time. In contrast, the phylum Deinococcus-Thermus and the Sphingomonadales (Alphaproteobacteria) were significantly more abundant on rocks, where they may benefit from using sugar alcohols and organic acids released by lichenized fungi, molds and algae (Siebert and Hirsch, 1988;Brewer and Fierer, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…We used both high‐throughput amplicon (targeting the 16S rRNA gene) and whole metagenome shotgun sequencing on stone ruins from three distinct climates in Tunisia and Algeria to achieve our objectives. Although climate has been shown to have an impact on stone microbes of the Mediterranean basin (Macedo et al ., ), most previous research on the microbiome of stone structures of Europe, North America, and South America has instead focused on stone geochemistry as drivers of diversity and functional variation (Cockell et al ., ; Krakova et al ., ; Chimienti et al ., ; Brewer and Fierer, ; Gaylarde et al ., ,b). In this study, we aimed to determine what aspects of the climate, including precipitation, temperature and others, were associated with specific microbial community variation, particularly in representation of Actinobacteria and Cyanobacteria colonizers.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [41] considered Sphingomonas a major player in the deterioration of monuments because of its high relative abundance and frequency on heritage stone [42]. However, this genus has been also retrieved in dust samples which may explain its global presence on stone substrata [43,44]. Indeed, Sphingomonas and Quadrisphaera, a recently identified actinobacterium [45], were isolated from Antarctic samples [46].…”
Section: Discussionmentioning
confidence: 99%